La opresión y los espacios urbanos en el cuento Los Gallinazos Sin Plumas de Julio Ramón Ribeyro - Benites Cerna, Maryury Tatiana (2017)
The present thesis aims to demonstrate how oppression manifests itself in a society of changes and imposition of capitalism and to point out the urban spaces in the story Los gallinazos sin pens of Julio Ramón Ribeyro, who is one of the representatives of the urban narrative and describes with much mastery of the various psychological types and social classes of Lima._x000D_ Ribeyro's narrative reflects themes such as oppression, exploitation, misery in a world of Lima city; This is reflected in the story of our work, whose protagonists are the old Don Santos, an old oppressor towards his two little grandsons Enrique and Efrain who look for rubbish in the street the midden to feed an insatiable pig._x000D_ Ribeyro's narrative unfolds in the 50's, in a world full of conflicts of the marginal population, where he narrates the daily life of that time. Therefore it is the one that deals with subjects of environment, personages or situations of the city, where it reflects the problems and feelings of the man to the big cities.